Caring for children and adolescents with type 1 diabetes mellitus: Italian Society for Pediatric Endocrinology and Diabetology (ISPED) statements during COVID-19 pandemia. (October 2020) - d'Annunzio, Giuseppe; Maffeis, Claudio; Cherubini, Valentino; Rabbone, Ivana; Scaramuzza, Andrea; Schiaffini, Riccardo; Minuto, Nicola; Piccolo, Gianluca; Maghnie, Mohamad
Abstract: Aims: Our study aimed to review the impact of COVID-19 pandemia in children and adolescents with type 1 diabetes mellitus, to analyze the clinical characteristics of the infection and to propose clinical practice recommendations from the Italian Society for Pediatric Endocrinology and Diabetology (ISPED). Methods: A literature search was carried out in the guideline databases, Medline and Embase and in Diabetes Societies websites until May 21st, 2020 for guidelines and recommendations on type 1 diabetes mellitus management during COVID-19 pandemic. Results: COVID-19 infection in pediatric patients seems to be clinically less severe than in adults; children have so far accounted for 1–5% of diagnosed cases, with a median age of 6.7 years (1 day–15 years) and better prognosis. Clinical manifestations include mild, moderate, severe disease up to critical illness. There is currently no evidence suggesting a higher risk of COVID-19 infection in children with diabetes than unaffected peers. Besides general recommendations for pediatric patients, ISPED has proposed specific measures for patients with diabetes. Conclusion: COVID-19 outbreak modified type 1 diabetes management, and telemedicine has been demonstrating to be an effective new tool for patients care. Moreover psychological aspects deserve attention and future researchs are mandatory.